ECONOMICS OF CULTURAL GOODS: MARKET FOR CULTURAL AND VISUAL ARTS IN INDIA - Younus K, Mohammed (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This alrticle discusses economics of cultural goods, sepcifically, visual arts, in case of India. The theoretical discussion on this question covers, often categorized traditionally, economic goods and non-economics goods. The production and marketing mechanism in respect of these two goods is subjected to indepth analysis. The case of cars prices and winning value of paintings is taken to support the arguemnt made in this article. The methodology followed is basic in nature. The prices of cars and paintings are analysed based on decriptive statistics. The results demonstrate that these two goods, though differently priced, obey laws of production and marketing within the framework of economic process. The findings of the article strengthens the argument that there are no goods which are ecxeptional to the laws of economics once they are subjected to transaction by exchange. The article conludes that cultural goods though unique in their own way comes within the scope of economic system